Community Supervision of Drug-Involved Probationers in San Diego County, California, 1991-1993 - Hoctor, Darlanne ([Verlag nicht ermittelbar], 2000)
The Probationers in Recovery (PIR) program, developed by the San Diego County Probation Department, targeted high-risk, drug-abusing offenders with the goal of controlling offender behavior without increasing risks to communities. This evaluation of PIR was based on a quasiexperimental design that compared program activities and outcomes for two matched groups of high-risk probationers receiving different levels of service and supervision. The assessment included both a process evaluation to discover if expected service levels were implemented as designed, and an impact evaluation to assess the effectiveness of drug treatment within an intensive community supervision program. The experimental group included 209 PIR participants who received intensive community supervision and drug treatment, and the control group consisted of 151 probationers who were assigned to regular high-risk probation caseloads and who met the PIR screening criteria. The samples were selected from probationers entering community supervision from February to December 1991. The length of the PIR program varied, but for purposes of analysis the minimum time in the program to represent the intervention period was set at eight months, including relapse prevention. A comparable period was used for the control group. The subsequent six-month period was used to measure the effects of PIR and regular high-risk probation after intervention. Intake interviews were conducted with a subsample of 96 probationers in PIR and 80 in the control group (Part 1). The interviews were conducted within the first two weeks after intake. Follow-up interviews were conducted with these probationers after they had completed eight months of PIR or regular high-risk probation to measure experiences on probation and changes in behavior and attitudes (Part 2). Follow-up interviews were completed with 47 probationers from the experimental group in the PIR program and 35 in the control group. The case tracking portion of the study involved the review of probation, treatment, and state and local criminal history files (Part 3). Data on technical violations and arrests for new crimes were compiled for the following time periods: (1) six months prior to the instant offense (the baseline), (2) the first eight months of community supervision (the in-program period), (3) the six months after intervention, and (4) the combined 14-month period. The initial interview (Part 1) included questions regarding sociodemographic characteristics, current offense, awareness of probation conditions ordered, perceived consequences for violations of probation, drug use and drug history, prior drug treatment and treatment needs, criminal history, expectations regarding the probation term, opinions regarding probation and treatment, daily activities prior to the current offense, current life satisfaction, and prospects for the future. Questions on the follow-up interview (Part 2) focused on changes in probationers' personal lives (e.g., employment, income, education, marital status, living situation, and relationships with family and friends), technical probation violations and new offenses committed during the eight-month period, sanctions imposed by probation staff, contacts with probation and treatment staff, changes in drug use and daily activities, expectations with regard to remaining crime- and drug-free in the future, attitudes regarding probation and treatment, treatment needs, and significant life changes over the eight-month period. Variables in the tracking data file (Part 3) include sociodemographic characteristics, current offense and sentence imposed, probation conditions ordered, drug use history, offense and probation violations occurring before, during, and after an eight-month probation period, custody time, changes in level of probation supervision, and program interventions such as drug tests, services delivered, and sanctions imposed.